The influence of tidal activities on water quality of paka river Terengganu, Malaysia [Pengaruh aktiviti pasang surut kepada kualiti air sungai paka Terengganu, Malaysia] - Muhammad Barzani, Gasim; Nadila, Abdul Khalid; Haniff, Muhamad (Malaysian Society of Analytical Sciences, 2015)
A study to determine the water quality at seven stations was carried out on the Paka River, Terengganu between two tides. Sampling begins from the estuary of the Paka River, and ended about 14 km from the mouth by a distance 2 km for each station. Sampling was carried out between two tides (high and low tides) and within two variations of time representing the first sampling (wet period) and the second sampling (dries period). Water quality parameters such as temperature, dissolved oxygen, conductivity, salinity, pH and total dissolved solids (TDS) were measured directly in the field using multiparameter the YSI 556. Analysis of sodium, magnesium sulfate was carried out according to the APHA and HACH methods. Determination of primary data and physicochemical characteristics of the River Paka are measured and analyzed for each sampling station. Physicochemical parameters such as temperature, pH, dissolved oxygen, total dissolved solids, salinity, electrical conductivity, sodium, and magnesium sulphate concentration were used to determine its relationship of the movement of tides and other factors that affect water quality. Station 1 shows the highest reading physicochemical parameters than station 7 during the first and second samplings. The higher reading most of physicochemical parameters was also observed during the dry season, this is because the river flow from upstream was decline due to low rainfall intensity.